The Role of Banking Governance in Guarantee of Credit Risks - حسين, أكرم محمد; شويش, أبرار عبد الحسين (Journal of Legal Sciences, 2019)
Risks are linked to banking activities. In order to overcome these risks, the bank has only the ability to rely on guarantees that are various and varied. These include traditional guarantees such as personal guarantees, commercial and real estate mortgages, insurance operations, specialized to cover the risks of foreign trade operations.Including the procedures and procedures that the banking institution should abide by in the practice of its credit activities both before and after the grant to detect the risks surrounding them early and address them before they grow, by following the rules of banking governance of forming specialized committees in the bank, Monitoring credit operations and reviewing the credit portfolio to ascertain the extent to which the Bank's management is in compliance with the standards and criteria for granting credit and the obligation to disclose and transparency in its transactions.Our research highlights the role of banking governance in reducing or avoiding the risk of credit granting.